Simulasi Pengaruh Kadar Air Tanah terhadap Parameter Mekanik untuk Desain Lereng Tanah di Bukit Tui, Kelurahan Tanah Hitam, Kecamatan Padang Panjang Barat, Kota Padang Panjang, Provinsi Sumatera Barat - Ahmad Abdillah; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Tui Hill is a limestone hill lined south of Padang Panjang. The results of investigations on the slopes of Bukit Tui at the location of S0 ° 28 '18.5 "E100 ° 23' 54.7 located in Tanah Hitam, have cracking of 20 m long, 1.5 m deep, 60 cm wide. This study aims to design a safe slope design by considering changes in mechanical parameters (cohesion and inner shear angle) due to increased soil water content. From several simulations of increasing water content values, slope FK calculations were performed. The calculation results show that in the original condition FK 1.632 was obtained, for the simulation of increasing the water content value, additional water from 5% to 20% was carried out. The addition of 5% water was obtained by FK 1,567. 10% water addition was obtained FK 1.425, 15% water addition obtained FK value 1.2273, 20% addition of water obtained FK 1.080. For the safe slope design FK values were taken in the condition of adding 20% moisture content, FK = 1.080. Based on this consideration, stable slope conditions can be achieved by reducing the slope with a slope consisting of three levels with a height of 15 m and a slope of 380, the second level with an altitude of 10.003 m and slope 400, the last level with a height of 10 m and slope 360.   Keywords: Slope Stability Analysis, moisture content, safety factor (FK), cohesion, inner sliding angle